Sleep and mental health during the COVID-19 pandemic: findings from an online questionnaire survey in China - Liu, Xuqian; Liu, Mingyue; Ai, Guangyuan; Hu, Naijun; Liu, Wenhan; Lai, Chao; Xu, Feng; Xie, Zhaohong (Frontiers in Neurology, 2024)
Introduction The online study investigated the sleep, psychological conditions, and risk factors during the wave of transmission of COVID-19 since December 7, 2022. Methods We distributed questionnaires through networking mediums to residents to gather information about COVID-19 infection, sleep, and mental status. Results During the extraordinary period in China, 91.9% of 1094 participants claimed to be infected with COVID-19, 36.8% reported poor sleep quality, 75.9% reported anxiety, and 65.5% reported depression. In retrospect, people have experienced lower sleep quality, longer sleep latency, enhanced rising time, and decreased sleep efficiency after the infection wave. After adjusting confounding factors, the elderly, women, urban residents, people with comorbidity, anxiety, depression, stress state, and COVID-19 infection have high risks for sleep disorders during the period. Discussion The survey indicates that sleep disturbance caused by COVID-19 involves multiple dimensions, such as physiology, psychology, and society. The COVID-19 infection-related sleep problem should be taken seriously. Apart from conventional treatment, psychological issues of insomnia can not be ignored.